Congestive heart failure adherence redesign trial: a pilot study - Ashvarya Mangla; Rami Doukky; Lynda H Powell; Elizabeth Avery; DeJuran Richardson; James E Calvin (BMJ Open)
Objective Heart failure (HF) continues to be a leading cause of hospital admissions, particularly in underserved patients. We hypothesised that providing individualised self-management support to patients and feedback on use of evidence-based HF therapies (EBT) to physicians could lead to improvements in care and decrease hospitalisations. To assess the feasibility of conducting a larger trial testing the efficacy of this dual-level intervention, we conducted the Congestive Heart failure Adherence Redesign Trial Pilot (CHART-P), a proof-of-concept, quasi-experimental, feasibility pilot study.Setting A large tertiary care medical centre in Chicago.Participants Low-income patients (<US$30 000/year) hospitalised for exacerbation of systolic HF (ejection fraction ≤50%) and their physicians. Twenty physicians and 33 patients were enrolled, of whom 23 patients completed the study.Interventions Physicians received HF guidelines and periodic individualised feedback on their adherence to EBT. Patients received HF education, support and self-management training for diet and medication adherence by a trained nurse through 11 interactive sessions over a 4-month period. Evaluations were conducted pre-enrolment and 1 month postintervention completion.Outcome measures Feasibility was assessed by the ability to deliver intervention to patients and physicians. Exploratory outcomes included changes in medication and sodium intake for patients and adherence to EBT for physicians.Results Eighty-seven per cent and 82% of patients received >80% of interventions at 1 month and by study completion, respectively. Median sodium intake declined (3.5 vs 2.0 g; p<0.01). There was no statistically significant change in medication adherence based on electronic pill cap monitoring or the Morisky Medication Adherence Scale (MMAS); however, there was a trend towards improved adherence based on MMAS. All physicians received timely intervention.Conclusions This pilot study demonstrated that the protocol was feasible. It provided important insights about the need for intervention and the difficulties in treating patients with a variety of psychosocial problems that undercut their effective care.